Perancangan Label Kemasan UMKM Kirihuchi Sebagai Media Promosi Untuk Meningkatkan Pemasaran Produk - Soedewi, Sri; Mustikawan, Arry; Swasty, Wirania; Mohd Pahme, Nur Faizah; Mohd Shuib, Ahmad Sofiyuddin (Visualita Jurnal Online Desain Komunikasi Visual, 2024)
Product packaging is an effective marketing tool that can influence buyer decisions, increase product selling value, and increase sales. The packaging of the Kirihuci, MSME product from Bandung produces chips made from Cilembu sweet potato has little selling value because it only uses ordinary plastic with packaging labels attached and does not contain complete information needed by consumers. The problem is Cilembu sweet potato chips are prone to breakage. Design packaging and attractive packaging labels are necessary to keep good quality of food and influence consumers. Qualitative research methods are used by conducting observations, interviews, and literature studies to collect design audits and obtain creative briefs. Then the analysis is carried out to get the packaging design references. The research is to purpose a packaging design with the Primary Display Panel standards (color, typography, visuals, and elements on the packaging). So, it can influence consumer purchasing decisions and can improve product marketing.